ACROSS-THE-BOARD WAGE INCREASES IN EXTENDED COLLECTIVE AGREEMENTS: FAIR OR UNFAIR? - Julien Hofman (Obiter, 2021)
The article looks at across-the-board increases in collective agreements extended to employers who were not party to the negotiations that produced them. It asks whether having to pay such increases can be unfair to these employers. The article explains the safeguards in section 32 of the Labour Relations Act. It concludes that, although these safeguards are not as clear as they might be, they should protect employers from having to pay unfair across-the-board increases. The article ends by looking at how to simplify the safeguards in section 32.